PERTUMBUHAN BIJI KAKAO (Theobroma cacao L.) DENGAN VARIASI KONSENTRASI AIR KELAPA DAN LAMA WAKTU PERENDAMAN - Mukarlina Mukarlina; Riza Linda; Siska Siska (BUANA SAINS, 2021)
Cocoa (Theobroma cacao L.) is a commodity of plantation crops that plays a primary role in the Indonesian economy. This study aimed to determine the growth of cocoa beans (Theobroma cacao L.) with different variations in coconut water concentration and length of soaking time. Treatments tested in this study used two levels of treatment. First factor was coconut water concentration (A) consisting of control (0%), (30%), (60%), and (90%). The second factor of soaking time (B) consisted of control (0 hours), (16 hours), (20 hours), (24 hours), and (28 hours). The result showed that combination treatment of coconut water solution 60% + 24-hour soaking showed the best results for all parameters of germination time (day), percentage of germination day 14, length of sprouts day 14, wet weight of sprouts day 14, the height of the plant day 28, wet weight of the 28th-day shoot and wet weight of the root of the 28th day.